Development of flavonoid probes and the binding mode of the target protein and quercetin derivatives. (15th August 2022) - Tsuchiya, Ayaka; Kobayashi, Miho; Kamatari, Yuji O.; Mitsunaga, Tohru; Yamauchi, Kosei
Graphical abstract: Abstract: This study investigated the mechanism underlying anti-cancer cell migration activity of quercetin derivatives by investigating the binding mode of the target protein. Five flavonoid probes were newly synthesized, and pull down assay using synthesized flavonoid probes indicated matrix metalloproteinase-1 (MMP-1) as the target protein of quercetin derivatives. Quercetin and 3- O -methylquercetin (3MQ) inhibited MMP-1. SPR analysis demonstrated dose dependent interaction between quercetin derivatives and recombinant MMP-1 catalytic domain. And 1 H- 15 N heteronuclear single quantum coherence (HSQC) NMR analysis using 15 N-labeled MMP-1 catalytic domain indicated that 3MQ interacted around metal ions in the MMP-1. The development of flavonoid probes can broaden the possibility to discover the new target proteins and elucidate the core mechanisms of the multi bioactivity of flavonoids.